ANALISIS PENGARUH RETURN PASAR DAN BEBERAPA VARIABEL MAKRO EKONOMI TERHADAP RETURN SAHAM INDIVIDUAL DAN PORTOFOLIO (Perbandingan Model Pasar, Model Makro-Ekonomi dan Gabungannya) - - Hasan (AKSES: Jurnal Ekonomi dan Bisnis, 2010)
The controversy about superiority of market model or multi-factors model keeps as interesting research theme in finance. This paper try to analyse some return generating models using several individual stocks and a portfolio composed from six listed stocks in Jakarta Islamic Index. The result shows that market model outperforms multifactors or macro model. In other words, market is reliable enough in generating predicted return.Keywords : return, market model, multifactors model,